Optimalisasi Penggunaan GIMP untuk Desain Grafis Digital Mahasiswa Teknologi Rekayasa Multimedia Grafis - Yunus Anis, Yunus; Sri Mulyani; Hersatoto Listiyono; Sunardi (JURNAL ABDIMAS SERAWAI, 2025)
The need for digital graphic design skills is becoming increasingly important in the creative industry era. However, limited access to paid software such as Adobe Photoshop is a challenge for students, especially in the Multimedia Graphic Engineering Technology (TRMG) Study Program on Universitas Stikubank Semarang. This Community Service Activity aims to optimize the use of GIMP (GNU Image Manipulation Program), open source software, as an alternative solution in developing digital graphic design skills. The method of implementing the activity includes intensive training, direct practice, and evaluation of design work results. The results of the activity showed a significant increase in mastery of GIMP tools, creativity in making designs, and time efficiency in completing projects. This activity is expected to encourage students to be more independent and adaptive to various design software, as well as increase their readiness in facing the challenges of the world of work